KARAKTERISTIK PERAIRAN MANGROVE PADA KERAPATAN YANG BERBEDA DI DESA EYAT MAYANG KABUPATEN LOMBOK BARAT - Diah Permata sari; Muhamad Husni Idris; Hairil Anwar; Irwan Mahakam Lesmono Aji; Kornelia Webliana B (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2023)
Different characteristics of mangrove habitat will have different water conditions. The purpose of this study was to determine the characteristics of mangrove habitat waters at different mangrove densities in Eyat Mayang Village, Lombok Barat Regency. Observation of mangrove density and characteristics of the waters was carried out in each sample plot using the grid line method. The tree parameters observed included the type and number of trees in the 84 sample plots. Parameters of mangrove habitat waters observed included temperature, pH, salinity, dissolved oxygen (DO) and mud thickness. Mangrove density is divided into 3 criteria based on the Decree of the Minister of Environment No. 201 of 2004. Furthermore, statistical analysis was carried out to assess differences in water characteristics at 3 mangrove densities using one-way analysis of variance with a level of 5% (significance 0.05) with SigmaPlot 11.0 software. The results showed that the sparse, medium and dense densities had an average temperature range of 29 ºC, a pH value of 6.8 – 7, a salinity in the range of 35‰, DO 4.8 – 5 mg/l and a mud thickness of 72 – 91 cm . The mangrove area of Eyat Mayang Village has 77.1% sparse tree density, 20% medium tree density and 2.9% dense tree density. The results of statistical analysis using the ANOVA test showed that there were no significant differences in the parameters of temperature, salinity, pH, DO and mud thickness at 3 different density of mangrove trees.